The bridge on the River Kwai - Spiegel, Sam.; Boulle, Pierre, 1912-1994; Holden, William, 1918-1981.; Guinness, Alec, 1914-2000.; Hawkins, Jack, 1910-1973.; d; Donald, James, 1917-1993.; Sears, Ann.; Horne, Geoffrey; Columbia Pictures; Columbia TriStar Home Video (Firm); Horizon Pictures (G.B.) (Culver City, Calif. : Columbia TriStar Home Video, 2000)
British soldiers captured by the Japanese during World War II are forced to construct a strategic railroad bridge which a commando team is instructed by the British High Command to destroy.
Based on the novel by Pierre Boulle.
Originally produced as a motion picture in 1957.
"Includes new footage"--Sticker on sleeve.
Rated PG.
Screenwriters, Michael Wilson and Carl Foreman ; music, Malcom Arnold ; director, David Lean.
William Holden, Alec Guinness, Jack Hawkins, Sessue Hayakawa, James Donald, Ann Sears, Geoffrey Horne.
Keywords: Burma-Siam Railroad -- Drama; World War, 1939-1945 -- Drama; War films; Feature films; Video recordings for the hearing impaired